The yasn ‘clan’ concept in the Kalmyk language - Esenova, Tamara S.; Esenova, Galina B. (The New Research of Tuva, 2024)
The article presents an analysis of the concept of the Kalmyk culture “yasn” ‘clan’. It shows that the ideas of kinship have various means of designation in Kalmyk language. The nominative field of this concept includes the following lexemes: “ang”, “aamg”, “yasn”, “otg”, and “arvn”.The conceptual content of “yasn”: ‘people of the same origin’, ‘one bone’, ‘one blood’. The family can be interrupted by the children of a daughter, or due to a curse. The son is the heir of the family.The figurative component of this concept is understood through a person. Well-born people and those with a good pedigree are distinguished from rootless people. The axiological component of a culture defines the norms of behavior and communication within and outside the family, ensuring the continuation of cultural and social traditions. Supporting members of one's own group is an important aspect of Kalmyk behavior. For the Kalmyks, members of their own group are associated with kinship, while others are considered strangers.
Keywords: concept of culture; component of concept; yasn; kinship; terminology of kinship; Kalmyks; Kalmyk language